2016
DOI: 10.1002/mbo3.401
|View full text |Cite
|
Sign up to set email alerts
|

Role of OmpA2 surface regions ofPorphyromonas gingivalisin host-pathogen interactions with oral epithelial cells

Abstract: Outer membrane protein A (OmpA) is a key outer membrane protein found in Gram‐negative bacteria that contributes to several crucial processes in bacterial virulence. In Porphyromonas gingivalis, OmpA is predicted as a heterotrimer of OmpA1 and OmpA2 subunits encoded by adjacent genes. Here we describe the role of OmpA and its individual subunits in the interaction of P. gingivalis with oral cells. Using knockout mutagenesis, we show that OmpA2 plays a significant role in biofilm formation and interaction with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…We performed invasion assays at an MOI of 1:100, and observed association and invasion rates of approximately 1%; typical of invasion rates our laboratory commonly observes for oral anaerobes such as Porphyromonas gingivalis, Tannerella forsythia , and Fusobacterium spp. (Naylor et al 2017). In contrast, assays performed in the presence of Zanamivir, displayed a dramatic, and statistically significant reduction in levels of total association (2.2-fold, p  = 0.03), adhesion (1.95-fold, p  = 0.04), and invasion (2.4-fold, p  = 0.03) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed invasion assays at an MOI of 1:100, and observed association and invasion rates of approximately 1%; typical of invasion rates our laboratory commonly observes for oral anaerobes such as Porphyromonas gingivalis, Tannerella forsythia , and Fusobacterium spp. (Naylor et al 2017). In contrast, assays performed in the presence of Zanamivir, displayed a dramatic, and statistically significant reduction in levels of total association (2.2-fold, p  = 0.03), adhesion (1.95-fold, p  = 0.04), and invasion (2.4-fold, p  = 0.03) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Invasion assays were performed as previously described (Naylor et al 2017). In brief, 2.0 × 10 5 HeLa cells were seeded in 24-well tissue-culture plates overnight in media without pen/strep, before washing with PBS and incubated for 1 h at 37 °C, 5% CO 2 in DMEM with 2% bovine serum albumin (BSA) (Sigma, Poole).…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, ΔAHA_1280 also increased the haemolytic activity in this study. The previous research reported that ΔompA2 in Porphyromonas gingivalis shows a reduction in biofilm formation higher than that of ΔompA1 and it plays a significant role interacting with human epithelial cells, which further supports our finding about the distinct biological functions among these OmpA family proteins (Naylor et al ., ). We previously reported that A0KHS0 ( AHA_1280 ) and A0KHS1 ( AHA_1281 ) have several lysine succinylation modifications sites but not A0KHR9 ( AHA_1279 ).…”
Section: Discussionmentioning
confidence: 97%
“…No significant differences were observed between either the ΔompA1 or the ΔompA2 deficient mutants when compared to the parent strain within CHRF-288-11 association as determined by antibiotic protection assays and flow cytometry. It has previously been shown that OMPA, specifically the OMPA2 subunit is fundamental for interactions between P. gingivalis and epithelial cells in vitro (Naylor et al, 2016). However the data produced within this chapter of work suggests that P. gingivalis interactions with CHRF-288-11 cells occur independently of either OMPA subunit, suggesting that both of the OMPA subunits can facilitate bacterial association with CHRF-288-11 cells independently.…”
Section: Discussionmentioning
confidence: 76%
“…Recently, the OmpA protein, specifically the A2 subunit, has been shown to contribute to both biofilm formation and host-cell interactions with epithelial cells (Naylor et al, 2016), with the ompA genes being upregulated in highly invasive populations of P.…”
Section: Outer Membrane A-like Proteinsmentioning
confidence: 99%